Attitudes of Primary Education Students toward Intercultural and Bilingual Education in Primary Schools - Hus, Vlasta; Hegedis, Polona Jancic (New Horizons in Education and Social Studies Vol. 9, 2021)
In this chapter, we present the research that analyses the attitudes of primary education students towards intercultural and bilingual education. Interculturality is a current social issue today and can be recognised as an ethic -political project aimed at solving problems of co-existence in multi-ethnic societies. Intercultural education is, therefore, an opportunity and a reason to change educational approaches. A key element for an education containing elements of intercultural education is bilingual education and a highly qualified primary school teacher. The research problem was examined from three different aspects. First, the students’ opinion on the applicability of intercultural and bilingual education. Second, the advantages and disadvantages of intercultural and bilingual education. And finally, the knowledge about intercultural and bilingual education in bilingual primary schools. The research results show that future primary school teachers believe in a good knowledge of intercultural and bilingual education and believe that this kind of education is the most appropriate and useful for the children of minorities to learn a foreign language. Moreover, the results show that primary school pupils have recognised that the ability to speak more languages and to have multi- and intercultural experiences is the advantage of intercultural and bilingual education. Half of the participating future teachers do not recognise any disadvantages of intercultural and bilingual education. In contrast, others recognise the additional obligations of teachers and possible specific learning problems of pupils as possible disadvantages.